2022
DOI: 10.1038/s41467-022-31270-y
|View full text |Cite
|
Sign up to set email alerts
|

Peptide fusion improves prime editing efficiency

Abstract: Prime editing enables search-and-replace genome editing but is limited by low editing efficiency. We present a high-throughput approach, the Peptide Self-Editing sequencing assay (PepSEq), to measure how fusion of 12,000 85-amino acid peptides influences prime editing efficiency. We show that peptide fusion can enhance prime editing, prime-enhancing peptides combine productively, and a top dual peptide-prime editor increases prime editing significantly in multiple cell lines across dozens of target sites. Top … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…In cultured mammalian cells, PEmax improves editing efficiency over PE2 by up to threefold on average. Sherwood and co-workers also increased cellular PE2 expression upon tethering peptides to PE2 70 . Using a high-throughput approach called PepSEq to identify candidate peptide fusions, they designed an IN-PE2 editor construct that shows improvement in mouse and human cell types (Fig.…”
Section: Enhanced Prime Editor Effector Proteinsmentioning
confidence: 91%
See 2 more Smart Citations
“…In cultured mammalian cells, PEmax improves editing efficiency over PE2 by up to threefold on average. Sherwood and co-workers also increased cellular PE2 expression upon tethering peptides to PE2 70 . Using a high-throughput approach called PepSEq to identify candidate peptide fusions, they designed an IN-PE2 editor construct that shows improvement in mouse and human cell types (Fig.…”
Section: Enhanced Prime Editor Effector Proteinsmentioning
confidence: 91%
“…Furthermore, Wang and co-workers designed extended pegRNAs containing a 3ʹ Csy4 recognition motif hairpin, which are likely to enhance prime editing through the same mechanism 77 . In their enhanced prime editing system (ePE), these extended pegRNAs are also fused to a nicking sgRNA and co-delivered with Csy4 nuclease, 70 , pegRNAs carrying the F + E crRNA scaffold 54,78 , and ePE pegRNAs 77 improve prime editor and pegRNA expression. epegRNAs 54 , ePE pegRNAs 77 , xr-pegRNAs 74 , G-PE pegRNAs 75 and sPE pegRNAs 76 reduce pegRNA degradation.…”
Section: Table 1 (Continued) | Prime Editor and Pegrna Architecturesmentioning
confidence: 99%
See 1 more Smart Citation
“…5 ). For the fusion of different peptides to PE2 25 , 26 , similar to GCN4, these peptides show a slight effect on PE system. Taken together, these studies appear contradictory but are consistent with our results.…”
Section: Discussionmentioning
confidence: 95%
“…Recent studies showed that the direct fusion of Rad51 DNA-binding domain 20 or various peptides 25 , 26 to PE2 generally increases the PE editing efficiencies. For the fusion of the Rad51 DNA-binding domain, the authors inserted Rad51 DBD into the region between nCas9 and RT domains, N- or C-terminus of PE2, generating variants named PE2-mid_Rad51, PE2-N_Rad51, and PE2-C_Rad5, respectively.…”
Section: Discussionmentioning
confidence: 99%